Pelatihan Penerapan Evaluasi Pembelajaran PPKn Untuk Penguatan Karakter Siswa di SMK PGRI 1 Denpasar - Sujianti, Ni Putu Ika Putri; Santika, I Gusti Ngurah; Ahas, Adrianus; Sila, I Made; Sutika, I Made; Lestari, Limas Dwi (Civiliza Publishing, 2025)
This Community Service (PkM) activity was carried out by the Pancasila and Citizenship Education Study Program, Faculty of Teacher Training and Education, Dwijendra University, as a form of implementation of the Tri Dharma of Higher Education. This activity aims to improve the quality of PPKn learning and strengthen student character at SMK PGRI 1 Denpasar through training on the application of learning evaluation. Based on the results of interviews with PPKn teachers, two main problems were found: difficulties in implementing learning reviewed from the aspects of planning, implementation, and evaluation, and obstacles in integrating character values into the learning process. The training activity was held on June 17, 2025, involving PPKn teachers, lecturers, and students. The training material focused on character-based learning evaluation strategies such as the values of responsibility, tolerance, and discipline. The results of the activity demonstrated the enthusiasm of participants in understanding and implementing character-based evaluation, as well as a commitment to implementing the training results in the school environment. As a follow-up, an online communication group was formed and the signing of the MoA and PkS was carried out as a form of ongoing collaboration. This activity is expected to make a real contribution to the development of teacher professionalism and improving the quality of character education in schools.